Діагностика медичних зображень пухлин з використанням гібридних нечітких згорткових нейронних мереж - Zaychenko, Yuriy; Hamidov, G.; Varga, I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The problem of classification of breast tumors on medical images is con-sidered. For its solution the new class of convolutional neural networks-hybrid CNN–FNN network is developed in which convolutional neural network VGG-16 is used as the feature extractor while fuzzy neural network NEFClass is used as the classifier. Training algorithms of FNN were implemented. The experimental investigations of the suggested hybrid network on the standard data set were carried out and comparison with known results was performed. The problem of data dimensionality reduction is considered and application of PCM method is investigated.